The Interest Of Family Welfare Science Department In Participating The Entrepreneurship Student Program In Universitas Negeri Padang - Yesa Silfia Sari; Asmar Yulastri (Universitas Negeri Padang, 2021)
The background of this research is the lower of student in participating the entrepreneurship student program in the Universitas Negeri Padang. The purpose of the research to describe of IKK department with family welfare education (first level cullinary system concentration) and cullynary academy study program interests. This type of the research is a Quantitatif descriptif. The population in the research is about 278 students with a sample of 74 people is taken based on proportional random sampling technique. Research data collection tecnique uses a quitionnnare design based on a likert scale that has been tested for validity and realibility. The data analysis technique will beusing microsoft office excel 2007 program and spss 17.0. The results of the analysisof the research data show that students interest in the program is at avarage level.